2020
DOI: 10.1097/mao.0000000000002425
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Speech Outcomes After Cochlear Implantation in Older Adults Using the Self-administered Gerocognitive Examination Test

Abstract: Purpose: The purpose of this study is to determine if a cognitive test, Self-administered Gerocognitive Examination (SAGE), correlates with speech recognition outcomes 1 year after cochlear implantation in adults over 65 years of age. Methods: Retrospective study was conducted at a single institution. Surgery was performed by two surgeons on adult patients (>65 yrs) with postlingual bilateral sensorineural hearing loss meeting clinical and audiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Factors that were predictive of better and/or more improved AzBio or CNC scores at various postoperative time points included “normal” SAGE cognition scores, younger age, and shorter duration of amplification. These findings are consistent with prior studies, which have previously demonstrated these relationships 21 . In our practice, all CI candidates with SAGE scores less than 17 are referred for neuropsychological evaluation prior to proceeding with implantation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Factors that were predictive of better and/or more improved AzBio or CNC scores at various postoperative time points included “normal” SAGE cognition scores, younger age, and shorter duration of amplification. These findings are consistent with prior studies, which have previously demonstrated these relationships 21 . In our practice, all CI candidates with SAGE scores less than 17 are referred for neuropsychological evaluation prior to proceeding with implantation.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with prior studies, which have previously demonstrated these relationships. 21 In our practice, all CI candidates with SAGE scores less than 17 are referred for neuropsychological evaluation prior to proceeding with implantation. While most patients were able to proceed with implantation with familial support, 2 patients with SAGE scores of 7 or less were not offered CI based on neuropsychological evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…These four more clinical tests, mostly used to detect early signs of Dementia (see Table 5a for an overview), are: (1) The Mini-Mental State Examination (MMSE) which did not significantly correlate with word perception in quiet ( r 2 = 0.061, p = 0.280, N = 15) ( Zucca et al, 2022 ). (2) The Self-Administered Gerocognitive Examination (SAGE), where preoperative screening of cognitive functions significantly positively correlated with word recognition in quiet [ r 2 (32) = 0.1955, p = 0.0025] and sentence perception in quiet [ r 2 (32) = 0.1564, p = 0.0067] and noise [ r 2 (32) = 0.1543, p = 0.007] ( Wazen et al, 2020 ). (3) The Montreal Cognitive Assessment (MoCA), which was included in a multivariate model explaining variance in sentence perception performance in noise.…”
Section: Resultsmentioning
confidence: 99%
“…These did not predict word perception in quiet with a sample size of 15 ( Zucca et al, 2022 ). However, research including a larger sample size (df = 32) ( Wazen et al, 2020 ) did show the effectiveness of a quick cognitive assessment for predicting sentence perception in quiet and noise preoperatively. Furthermore, it might be beneficial to consider social cognition, the only cognitive domain currently not covered in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Further, an association of auditory and cognitive performance following cochlear implantation has been rarely reported ( Cosetti et al, 2016 ; Wazen et al, 2020 ; Zhan et al, 2020 ; Knopke et al, 2021 ). Zhan et al found only a correlation of sentence recognition in quiet after 6 months with the incompatible Stroop and the Symbol Span test, but not for the Digits or Object Span test ( Zhan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%